2011
DOI: 10.1038/aps.2010.201
|View full text |Cite
|
Sign up to set email alerts
|

N-benzyl-5-phenyl-1H-pyrazole-3-carboxamide promotes vascular endothelial cell angiogenesis and migration in the absence of serum and FGF-2

Abstract: Aim: To investigate the effect of N-benzyl-5-phenyl-1H-pyrazole-3-carboxamide (BPC) on angiogenesis in human umbilical vein endothelial cells (HUVECs).Methods: Capillary-like tube formation on matrigel and cell migration analyses were performed in the absence of serum and fibroblast growth factor (FGF-2). Reactive oxygen species (ROS) were measured using a fluorescent probe, 2', 7'-dichlorodihydrofluorescein (DCHF). The nitric oxide (NO) production of HUVECs was examined using a NO detection kit. Morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Our results are in agreement with the literature (Xiong et al, 2019) that reported a novel thiazolyl substituted bis-pyrazole oxime compound selectively inhibited proliferation of colorectal cancer HCT116 cells by inducing apoptosis pathway through the promotion of intracellular ROS level. The therapeutic impact of a Pyrazole compound on angiogenesis in human umbilical vein endothelial cells (HUVECs) was studied by Zhang et al, (2011). They showed the Pyrazole compound induced angiogenesis by a significant increase of NO and ROS production through ROS-HIF-1α-VEGF and NO signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with the literature (Xiong et al, 2019) that reported a novel thiazolyl substituted bis-pyrazole oxime compound selectively inhibited proliferation of colorectal cancer HCT116 cells by inducing apoptosis pathway through the promotion of intracellular ROS level. The therapeutic impact of a Pyrazole compound on angiogenesis in human umbilical vein endothelial cells (HUVECs) was studied by Zhang et al, (2011). They showed the Pyrazole compound induced angiogenesis by a significant increase of NO and ROS production through ROS-HIF-1α-VEGF and NO signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The DCF assay is a popular method for assessing toxicant-stimulated generation of reactive oxidant species in cells (Bussche & Soares, 2011; Filipič & Hei, 2004; Gong & Han, 2006; Hatcher, et al, 2008; Hu, et al, 2011; Michalowicz, 2010; Naqvi, et al, 2010; Shanker & Aschner, 2003; Shao, et al, 2008; Wan & Winn, 2007; Zhang, et al, 2011; Zhu, et al, 2009). Although numerous caveats have been reported with the DCF assay, including effects of medium composition, serum, heme, heme proteins, metalloporphyrins and bovine serum albumin (Chen, et al, 2010), interactions with chemical toxicants have received nominal attention.…”
Section: Discussionmentioning
confidence: 99%
“…To test the secreted VEGF, the medium was replaced with 1 ml per well of fresh medium, and the cells were subjected to normoxia or hypoxia in the absence or presence of PAB for 12 h. Then, the cell supernatants were collected for ELISA assays with a VEGF-ELISA kit (Jingmei, Shanghai, China) as previously described [17].…”
Section: Elisa Assaysmentioning
confidence: 99%